Global, regional, and national burden of colorectal cancer associated with diet high in red meat, 1990 to 2021: an analysis for the global burden of disease study and prediction to 2036 - Huijun Lei; Miaomiao Chen; Haoyu Qu; Zuomei He; Hui Zhong; Liang Li; Mengzhou Xie (BMC Public Health)
Abstract Objective To evaluate the global, regional, and national burden of colorectal cancer (CRC) attributable to diets high in red meat from 1990 to 2021, project trends to 2036, and stratify findings by age, sex, and Sociodemographic Index (SDI). Methods Data on CRC burden associated with diet high in red meat were extracted from the Global Health Data Exchange (GHDx). Age-standardized rates (ASR) and estimated annual percentage change (EAPC) were calculated to assess temporal trends. Inequality slope and concentration indices quantified health disparities, while decomposition analyses identified drivers of burden changes. A Bayesian age-period-cohort (BAPC) model projected future trends through 2036. Results From 1990 to 2021, age-standardized mortality rates (EAPC = − 0.84%, 95% CI: − 0.87 to − 0.81) and disability-adjusted life years (DALYs) (EAPC = − 0.85, 95% CI: − 0.88 to − 0.81) for CRC attributable to high red meat intake declined globally. The reduction in DALYs was driven by decreasing years of life lost (YLLs; EAPC = − 0.9, 95% CI: − 0.93 to − 0.86), contrasting with rising years lived with disability (YLDs; EAPC = 0.45, 95% CI: 0.41–0.48). Males and older populations bore a disproportionate burden. Global population growth accounted for 99.73% of increased deaths, 112.77% of DALYs, 62.42% of YLDs, and 116.5% of YLLs. Inequality slope indices for mortality remained stable, while concentration indices for DALYs declined (deaths: 0.31 [95% CI: 0.28–0.34] to 0.26 [0.23–0.29]). Projections indicate declining age-standardized mortality and DALY rates by 2036, but absolute deaths, DALYs, and YLLs are expected to rise. Conclusion Despite declining age-standardized rates, the absolute burden of CRC associated with diet high in red meat persists, with marked disparities across regions and demographics. Population growth remains a critical driver, underscoring the need for targeted dietary interventions and equity-focused policies.